Performance of Laksmana Raja Di Laut Arranged by Julyani for Solo Marimba and Vibraphone - Youlanda, Mayank Rizkia; Marh, Fahmi; Herdianto, Ferry; Zaidi, Ahmad (Scoring: Journal of Film Music, 2024)
Laksamana Raja Di Laut is a Malay song composed by Datuak Suhaimi (Pak Ngah) in 1993, which was popularized and sung by Iyeth Bustami. This song was rearranged by Ijunk for marimba solo and vibraphone, with Big Band accompaniment format. The accompaniment format for marimba solo with vibraphone is complemented by traditional Malay drums. The musical arrangement of this song into a solo, uses a new musical concept that offers hybrid music (mixed music), through the naming of a new genre by the arranger, namely Progressive Malay, by adapting a free-form approach and variations of the theme. The arrangement of Admiral Raja di Laut uses a tighter notation with thirty-second notes to display the arranger's imagination with vibraphone and marimba about the sea and the prowess of a sailor from the Malay lands.